2019
DOI: 10.1111/hel.12596
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose PPI‐amoxicillin dual therapy with or without bismuth for first‐line Helicobacter pylori therapy: A randomized trial

Abstract: Background A reliably highly effective high‐dose proton‐pump inhibitor plus amoxicillin (dual Helicobacter pylori therapy) has remained elusive. We compared whether the addition of bismuth to high‐dose dual therapy would improve the efficacy of high‐dose dual therapy as first‐line treatment. Methods This was an open‐label, randomized single‐center study of 160 treatment‐naive patients with H. pylori infection who were randomly assigned to 14‐day therapy with esomeprazole 40 mg twice a day plus amoxicillin 1 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 37 publications
2
60
0
4
Order By: Relevance
“…Recently published two randomized controlled trials in China commonly revealed the favorable efficacy of high-dose amoxicillin containing regimens, irrespective of the addition of bismuth. 31,32 High-dose dual therapy including esomeprazole 40 mg bid, and amoxicillin 1 g tid with or without elemental bismuth 220 mg bid for 2 weeks showed comparable efficacy (over 90% eradication success in the PP analysis), irrespective of the antibiotic resistance. 31 Study of PAMB vs. PAM regimen including high dose amoxicillin (esomeprazole 20 mg bid, amoxicillin 1 g tid, and metronidazole 400 mg tid with or without 220 mg elemental bismuth bid) for 2 weeks also showed comparable efficacy (over 90% eradication success in the PP analysis), irrespective of the antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published two randomized controlled trials in China commonly revealed the favorable efficacy of high-dose amoxicillin containing regimens, irrespective of the addition of bismuth. 31,32 High-dose dual therapy including esomeprazole 40 mg bid, and amoxicillin 1 g tid with or without elemental bismuth 220 mg bid for 2 weeks showed comparable efficacy (over 90% eradication success in the PP analysis), irrespective of the antibiotic resistance. 31 Study of PAMB vs. PAM regimen including high dose amoxicillin (esomeprazole 20 mg bid, amoxicillin 1 g tid, and metronidazole 400 mg tid with or without 220 mg elemental bismuth bid) for 2 weeks also showed comparable efficacy (over 90% eradication success in the PP analysis), irrespective of the antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 High-dose dual therapy including esomeprazole 40 mg bid, and amoxicillin 1 g tid with or without elemental bismuth 220 mg bid for 2 weeks showed comparable efficacy (over 90% eradication success in the PP analysis), irrespective of the antibiotic resistance. 31 Study of PAMB vs. PAM regimen including high dose amoxicillin (esomeprazole 20 mg bid, amoxicillin 1 g tid, and metronidazole 400 mg tid with or without 220 mg elemental bismuth bid) for 2 weeks also showed comparable efficacy (over 90% eradication success in the PP analysis), irrespective of the antibiotic resistance. 32 Although metronidazole resistance can be overcome with the additive effect of bismuth, both bismuth and high-dose amoxicillin can both independently theoretically improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of a low-dose and/or less frequent dual therapy consisting of AMO (2.0 g/day or less) and PPI (twice/day or less) resulted in unacceptable eradication rates 32–34. Recently, high-dose and high-frequency dual therapy, defined as the administration of both AMO (≥2.0 g/day) and PPI (at least twice daily) for 14 days, has been reported to have greater H. pylori eradication efficacy as first-line therapy 35–38. However, side effects and poor patient compliance due to high dose, high administration frequency and long duration of treatment are the most common setbacks.…”
Section: Discussionmentioning
confidence: 99%
“…It should be borne in mind, however, that this applies to strains with low resistance levels (8-32 µg/mL), and higher resistance (>32 µg/mL) may reduce the effectiveness of this therapy from >90% to 60% [32]. Very promising results in the Asian population have been obtained for high-dose double therapy (AMX and PPIs), i.e., eradication rate >90% and low level of side effects (<15%) [33,34]. Avoiding the use of antibiotics with high frequency of resistance among H. pylori strains and the use of AMX, to which no resistance is currently observed in Poland, give hope for a wider use of this therapy.…”
Section: Discussionmentioning
confidence: 99%